Desarrollo turístico del Cantón Ventanas según su oferta turística - Hurtado Valero, Mallerly Paola (2020)
The present investigation was carried out in the Ventanas Canton, it is the fourth most populous canton, it has a population of 74,100 inhabitants, its extension is 533 km2 due to its rivers and riverbanks of which the canton is surrounded windows attract a lot of attention of citizens and tourists. It is the main canton that produces products such as corn which is the livelihood of the majority of its population, also produces products such as bananas, rice, cocoa, coffee, soybeans, passion fruit, gandul. Where the tourist offer was explored and the way in which it is influencing the development of tourism in the Canton The objective of this project is to analyze the tourism development and its relationship with the tourist offer of the Canton Ventanas. The applied research methodology was of bibliographic, field and descriptive type using the technique of direct observation and surveys, two instruments were also used; the formulation of surveys, population and sampling.